Dermatology development in russia and the ussr (1950-1959) - L. V. Belova-Rakhimova; V. I. Prokhorenkov; LN. . Guzei (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
History of dermatology development in Russia and the USSR in 1950-1959. words: dermatological service in Russia and USSR in 1950-1959.